Wakaf Virtual dalam Perspektif Pejabat Pembuat Akta Ikrar Wakaf: Tipologi Pemikiran PPAIW Ponorogo - Labib Suhaily; Miftahul Huda; Rohmah Maulidia (Institut Agama Islam Negeri Ponorogo, 2025)
The phenomenon of virtual waqf pledges carried out by the Waqf Pledge Deed Making Officer (PPAIW) of Jetis District, Ponorogo Regency, emerged amid a vacuum of formal regulations regarding virtual waqf, both in the Waqf Law, Government Regulations, and Indonesian Waqf Board policies. The urgency of this research lies in the differences in views among PPAIW regarding the validity and legality of virtual waqf pledges, which reflect the dynamics of Islamic legal thinking in the context of waqf digitalization. With a qualitative approach, this field research aims to explore the views of PPAIW in Ponorogo Regency regarding the virtual waqf pledge and analyze their thought patterns in responding to this phenomenon. Research data was obtained from informants from PPAIW Ponorogo. Data collection techniques were done through in-depth interviews, observation, and documentation. Data analysis was carried out using Mahsun Fuad's typological theory of Islamic legal thought, dividing the thought spectrum into participatory and emancipatory reasoning. The results of the research show that there are three typologies of PPAIW thinking regarding the virtual waqf pledge, namely: critical-responsive madzhabi reconstruction, emancipatory responsive-sympathetic interpretive reconstruction, and emancipatory responsive-sympathetic madzhabi reconstruction. This conclusion confirms the diversity of thought responses at the local level towards waqf practices in the digital era.